Adequacy of Financial Allocations for Recurrent Expenditures in Public Sector Schools of Punjab - Muhammad Afaq Durrez, Afshan Huma (JELM, 2023)
Public sector schools need finances to run their day-to-day activities. Budgets allocated to any school comprise a Salary Budget (SB) and a NonSalary Budget (NSB). Educational Institutions usually get NSB through financial tiers of provincial and district administration. It meets recurrent expenditures to include payment of utility bills, purchase of expendables, procurement of uniforms and books, purchase of stationery, minor maintenance work of school building, postage, and several other such expenditures. In the present security threatened scenario, NSB also includes the provision of security equipment which although not covered in existing rules but with an administrative order schools were asked to utilize this budget for the purpose. The covered area of school and locality has nothing to do with these allocations, whereas these factors play a pivotal role in increasing expenditures drastically because each school has a viariable area. Fewer allocations, coupled with increased recurrent expenditures, create a gap in meeting the school's overall output in delivering quality education. NSB allocation criteria need revision to meet the increased costs. This paper has brought forward the existing standards, including missing links, and has suggested ways to overcome these gaps and make allocation procedures more effective. It was a mixed research, descriptive in nature however qua